Investor mood and the determinants of stock prices: an experimental analysis. (9th March 2015) - Harding, Noel; He, Wen
Abstract: We examine, in a controlled experimental setting, whether changes in investor mood cause changes in the determinants of stock prices. Our results show that a deterioration in mood, reflected in the negative dimensions of mood state, increases the level of risk aversion in male, but not female, investors. We find no evidence to suggest that a change in mood impacts on investors' forecasts of future earnings or future cash flows. By establishing the causal impact of a change in mood on risk aversion, our study provides support for archival research that relates various market anomalies to investor mood.